Work locus of control as a mediator of the relationship between sources and consequences of occupational stress among university teachers - Slišković, Ana; Burić, Irena; Maslić Seršić, Darja (2011)
The paper deals with the relationship between specific sources of occupational stress, work locus of control, attitudes towards work, and well-being of university teachers. Work locus of control is defined as a situational variable which includes the perception of the level of control and free decision-making in the working context (Williams & Cooper, 1998), and its mediating role in relation to the sources and consequence of occupational stress is assumed. Research was carried out using an on-line questionnaire on a sample of teaching staff employed at four of the largest universities in Croatia (N = 1170). The presences of particular sources of stress at work were measured by the Questionnaire of Exposure to Occupational Stress for University Teaching Staff (ISR-SN). Job and organization satisfaction, perceived psychological and physical well-being and work locus of control were measured by the Croatian version of Pressure Management Indicator. Results of path analyses confirmed the assumption of partial mediation effects of the work locus of control on the relationship between the sources and consequences of occupational stress in university teaching staff.
Projekt MZOS
ENG